Analisis Perhitungan Harga Pokok Produksi Roti menggunakan Metode Full Costing: Studi Kasus Perusahaan Jo Bakery di Pringsewu, Lampung pada Tahun 2021 - Erik Susanto; Nurdiwansyah Nurdiwansyah (AKUNTANSI 45, 2024)
The purpose of this research is to analyze the calculation of the cost of production using the full costing method in 2021 at Jo Bakery Pringsewu, Lampung. With descriptive qualitative as a method of quantitative data analysis as well as the results of interviews and observations obtained from Jo Bakery. This study aims to find out the comparison between the calculation of the cost of production according to Jo Bakery with the calculation using the full costing method which is in accordance with accounting standards and see how much impact it has on selling prices. The results of the calculation using the full costing method show that the cost of production of Jo Bakery is greater because all the complete costs are calculated to be summarized into the right results without any unpaid expenses so that it gives a real time comparison of production costs, this is very useful for management and business continuity.